2022
DOI: 10.3390/jzbg3030026
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Space Use and Fecal Glucocorticoid Concentrations during and after the COVID-19 Closure to Investigate Visitor Effects in Multiple Species

Abstract: We used the COVID-19 pandemic closure at the Saint Louis Zoo to examine visitor effects on space use and glucocorticoid levels in banteng, grizzly bears, polar bears, and western lowland gorillas. The study was divided into four six-week phases: closure in spring 2020, reopening in summer 2020, fall 2020, and spring 2021 as a seasonal comparison. Space use data were collected using video, and fecal samples were assayed for glucocorticoids. Generalized linear models were used to examine differences in zone occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Similar changes to enclosure use have been observed in some species when zoological facilities opened after the COVID-19 facility closures [39,40]. However, behavioural changes did not always correspond with increased cortisol, which suggested animals were behaviourally controlling their stress levels caused by the changing environmental situations [13,15]. This research further supports the importance of enabling animals to make choices within their environments.…”
Section: Capybarasupporting
confidence: 70%
See 1 more Smart Citation
“…Similar changes to enclosure use have been observed in some species when zoological facilities opened after the COVID-19 facility closures [39,40]. However, behavioural changes did not always correspond with increased cortisol, which suggested animals were behaviourally controlling their stress levels caused by the changing environmental situations [13,15]. This research further supports the importance of enabling animals to make choices within their environments.…”
Section: Capybarasupporting
confidence: 70%
“…When conducted in person or via camera feeds, behavioural observations have the added benefit of enabling facilities to find out 'instantly' the impacts of evening events and act accordingly to support good animal welfare. However, assessment of physiological measures, principally analysis of faecal glucocorticoid metabolites (FGMs), has indicated that animals are less affected by the presence of visitors than their behaviour signifies [13][14][15], which may also explain the range of behaviour changes during evening events, with animals adapting to reduce the impacts of stressors related to evening events. Several behavioural changes have been observed within primate species.…”
Section: Introductionmentioning
confidence: 99%
“…Enclosure use alongside behavior was also explored in published literature in relation to visitor presence, with meerkats (Suricata suricatta) using more of their exhibit areas during periods of zoo closure, whilst space use for African penguins (Spheniscus demersus) was unaffected [19]. Additionally, space utilization combined with fecal glucocorticoid concentrations revealed an intra-individual difference in response to zoo closure for banteng (Bos javanicus), with a temporary elevation in glucocorticoid concentrations for two of the five animals studied and an increase in time spent close to visitor areas when zoo-visitors returned after closure [16]. Studies also varied in length, with some outlining a shorter pre to post closure comparison [20] whilst others looked more longitudinally, assessing seasonal differences in behavior alongside changes in visitor density [21].…”
Section: Introductionmentioning
confidence: 92%
“…In 2020, the outbreak of COVID-19 forced zoos around the globe to close their doors to visitors for an extended period. Despite these circumstances, the abrupt and prolonged closure of zoos and aquaria worldwide provided a unique opportunity to investigate the effect that visitors may have on zoo-housed species [14][15][16]. For example, during this period, visibility of amphibian species was suggested to be influenced [17] whilst differences in behavior were attributed to seasonal rather than visitor effects for two species of flamingo (Phoenicopterus roseus and Phoenicopterus chilensis) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst research across primates and other taxa has shown the adaptability of zoo animals and highlighted their ability to habituate to the presence or absence of zoo visitors [ 5 , 28 , 29 , 30 ], it is widely accepted that zoo visitors have varying impacts on zoo animals. The zoo animal–visitor dynamic is complex and there are a number of factors which are likely to impact the valence of these interactions for zoo animals, including but not limited to, previous experience with zoo visitors, behavioural ecology, individual personality and rearing history, enclosure design, husbandry and presence or absence of enrichment [ 5 , 10 , 20 , 22 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%